Social Network Analysis Of White Cooden Oil Producers In Sawa Village, Lilialy District, Buru District - Alisa Umamiti; A. E. Pattiselano; Paulus M. Puttileihat (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to analyze the characteristics of eucalyptus oil production and analyze the network structure, role of actors and centrality of eucalyptus oil producers in Sawa Village, Lilialy District, Buru Regency. This research uses qualitative research methods using a descriptive approach. This research was carried out in Sawa Village, Lilialy District, Buru Regency. The sample in this study were 20 eucalyptus oil producers. The data collection techniques used in the research were interviews, observation and documentation with data analysis used being data reduction, data presentation and drawing conclusions. The research results show that 1) the characteristics of eucalyptus oil producers in Saswa Village are: 7 (31.81%) respondents aged 41 – 50 years. All respondents (100%) were male. as many as 12 (54.54%) respondents had elementary school education. as many as 10 (45.45%) respondents with capital of more than Rp. 3,000,000. as many as 10 (45.45%) answered with a net income of Rp. 3,000,000- 4,000,000. 2) social network of eucalyptus oil producers in Sawa Village, namely: Social network structure based on trust and kinship. The actors involved in the social network of eucalyptus oil producers are land owners, eucalyptus oil producers and consumers. Sentalitis is not involved in eucalyptus oil producers because eucalyptus oil producers do not cooperate with the government in uniting produce.